Niger Spring 2021 Economic Update : Maximizing Public Expenditure Efficiency for Rebuilding Better - World Bank (World Bank, Washington, DC, 2021)
The ongoing health and security crisis have partly undermined the benefits from past years of strengthening economic growth. Sustaining an upward trend over the recent years, real growth stood at 5.9 percent in 2019. However, it fell to 3.6 percent in 2020, because of the pandemic and increasingly violent terrorist attacks. Inflation increased to 3.4 percent in 2020, triggered by supply disruptions and speculative behaviors, combined with food shortages. The economy is projected to rebound in 2021, growing at 5.5 percent, with the reopening of the border with Nigeria and the resumption of large investment projects and a normalization of other supply chains. The large import content of these projects will cause the current account deficit to widen further while completion of the main oil pipeline by 2023 should boost revenue and exports over the medium term. However, GDP per capita in 2021 will be only 1 percent higher than in 2019. Addressing inefficient management of a universal fertilizer subsidy program could generate fiscal savings of 0.15 percent of GDP. Until September 2020 fertilizers were sold by Central Agricultural Input and Equipment Supply Agency (CAIMA) and were on average half universally subsidized without targeting specific farmers or crops. The system was characterized by large inefficiencies, including inefficient fertilizer acquisition cost, incapacity to meet the demand and rising operating expenses. After having removed the management of fertilizers from Caima’s mandate, it is important that the Government finalize the ongoing work with development partners for a fertilizers reform that allows a better targeting the subsidies and gives a greater role for the private sector in the fertilizers supply and distribution.